A near-infrared reflectance spectroscopy–based nondestructive technique for the detection of seed-borne fungi in choy sum (Brassica chinensis var. Parchinensis) - Chen, Bijuan; Li, Guilian; Xiong, Zheng; Xiong, Yihao; Xu, Can; Xiong, Binghong (Bangladesh Journal of Botany, 2023)
In the present study seed-born fungi in choy sum (Brassica Chinensis Var. Parchinensis) was detected through a near-infrared reflectance spectroscopy–based nondestructive technique. Four common species of seed-borne fungi namely, Penicillium decumbens, Penicillium namyslowskii, Lichtheimia corymbifera, and Aspergillus niger were found to grow in choy sum in southern China. A novel finding was that P. decumbens had the greatest inhibition of the germination of Choy sum seeds, resulting in a non-germination rate exceeding 62.8%. The existing standardized seed sterilization treatment failed to completely kill P. decumbens, so a way to nondestructively identify and filter out P. decumbens–infected seeds wereevolved is urgently needed. Near-infrared reflectance spectroscopy–based partial least squares–discriminant analysis (PLS-DA) model achieved a discrimination accuracy of 95% in on-line nondestructive detection of P. decumbens–infected choy sum seeds. By detailing the design and application of an innovative product, this study lays a foundation for the development of intelligent equipment, and it provides a decision-making basis for seed breeding industrialization and germplasm supervision. Bangladesh J. Bot. 52(2): 689-694, 2023 (June) Special